REVIEW OF SHARIA ECONOMIC LAW ON THE WORKERS' WAGE SYSTEM - Reza Maihendra; Iskandar syukur; Gatot Bintoro Putro Aji (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study examines the wage system for workers in Jaya Screen Printing Pelastik Desa Negara Ratu, Natar District, South Lampung Regency from the perspective of Islamic economic law. Using a descriptive-analytical qualitative approach, data was collected through in-depth interviews with seven informants, direct observation, and documentation during February-April 2025. The results showed that the company implemented two wage systems: wage per unit (Rp5,000-8,000/kg) for operators and screen printing assistants, and daily wage (Rp70,000-80,000) for drivers and assistants. This creates a significant income gap, with workers earning IDR 40,000-96,000 per day compared to a fixed daily wage for an equivalent 8-hour workload. Critical findings included the absence of written employment contracts for all 11 workers, with wage agreements made orally. Analysis based on the principles of Islamic economic law shows inconsistencies in four main aspects: the justice of distribution (al-'adl) is violated because wages are disproportionate; the clarity of the contract (al-'aqd al-mubin) does not exist, creating gharar (uncertainty); voluntary agreements (al-taradhi) are disrupted by the weak bargaining position of the workers; and the accuracy of the payment is not in accordance with the hadith of the Prophet, which requires immediate payment of wages. The study concluded that the wage system does not meet the requirements of the ijarah contract, especially related to clear ijab qabul and fair ujrah, which has the potential to involve zulm (oppression) and exploitation of workers. Recommendations include the development of a standard ijarah contract template with minimum wage provisions based on the South Lampung Regency Minimum Wage (Rp2,889,193/2024), the implementation of a hybrid wage system that combines a fixed basic wage with productivity incentives, as well as the establishment of a government program that provides sharia-compliant employment contracts and halal wage certification for micro enterprises.